E-participation among members of parliament in Malaysia: evaluation of social factors / Norsyahida Zaharudin - Zaharudin, Norsyahida; Bakar, Ahmad Naqiyuddin; Hashim, Rugayah; Ambali, Abdul Raufi (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The purpose of this paper is to provide insights and empirical evidence on internet usage among the Members of Parliament (MP) in Malaysia In tandem with the globalization, Information and Communication Technology (ICT) usage has become ubiquitous. As such, politicians and MPs should fully utilize the internet-based tools to reach out to their constituent members. The Parliament of Malaysia, in responding to this phenomenon has provided the infrastructure for more e-engagement and e-participation, In addition, social factor such as norm and interpersonal message are also important to influence the individual behavior, participation and JCT engagement. Therefore, the objective of the study is to examine the relationship between social factors (subjective norm and word of mouth) and the MPs engagement. Through cross sectional design, the sample size was 222 MPs from the House of Representative in Malaysia and data collections were done through interviews, surveys and the evaluation of the MPs personal web site,